2019
DOI: 10.1519/jsc.0000000000002269
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Gaelic Football Match-Play Running Performance

Abstract: Mangan, S, Ryan, M, Shovlin, A, McGahan, J, Malone, S, O'Neill, C, Burns, C, and Collins, K. Seasonal changes in Gaelic football match-play running performance. J Strength Cond Res 33(6): 1686–1692, 2019—Time of season influences performance in many team sports; however, the anomaly has not yet been examined with regards to elite Gaelic football. Global positioning systems (4 Hz; VX Sport, Lower Hutt, New Zealand) were used to monitor 5 elite Gaelic football teams over a period of 5 years (2012–2016). In total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
17
2
1
Order By: Relevance
“…The highest total distances covered by elite Gaelic footballers has been found to occur during the final stages of the All-Ireland championship (Mangan et al, 2017b). Not surprisingly, the mean relative distance covered in this pre-season study was lower than the values reported previously (Malone et al, 2017b;Malone et al, 2016), although specific factors may have contributed to this underestimation.…”
Section: Discussioncontrasting
confidence: 70%
“…The highest total distances covered by elite Gaelic footballers has been found to occur during the final stages of the All-Ireland championship (Mangan et al, 2017b). Not surprisingly, the mean relative distance covered in this pre-season study was lower than the values reported previously (Malone et al, 2017b;Malone et al, 2016), although specific factors may have contributed to this underestimation.…”
Section: Discussioncontrasting
confidence: 70%
“…Through combining team performance data analysis, interpretations can be contextualised in a manner that is not possible when either physical or technical results are examined in isolation. Furthermore, the results extend recent analysis pertaining to specific aspects of both team [2,[16][17][18]33] and player performances [15,17,34]. From a physical perspective, the main findings from this study reveal that total distance covered was higher in games and halves lost.…”
Section: Discussionsupporting
confidence: 85%
“…Also, players competing in the latter stages of the AIC (i.e. August and September) covered significantly more total distance and distance at high speed in Q4 compared to all other months [15], suggesting that progressive conditioning and the enhanced profile of the AIC competition may facilitate superior levels of physical performance compared to those observed earlier in the season. Unfortunately, in these studies interpretation of the physical data may be limited due to the absence of information relating to temporal changes in technical performance.…”
Section: Introductionmentioning
confidence: 94%
“…Our findings suggest that players within these positions may look to CHO + CAF supplementation to maintain their ability to complete repeated sprint efforts as duration increases. Repeated sprint performance is also a key performance outcome in relation to other high intensity intermittent field sports such as Gaelic football and soccer [ 42 , 46 ]. Considering that CHO + CAF supplementation can potentially improve repeated sprint ability in hurling, these finding may translate appropriately for practitioners involved within these sports.…”
Section: Discussionmentioning
confidence: 99%